Analisis Kinerja Ruas Jalan Akibat Hambatan Samping (Studi Kasus : Jalan Soekarno Hatta, Labuhan Bajo, Manggarai Barat): Road Performance Analysis Due To Side Obstacles (Case Study: Soekarno-Hatta Road, Labuhan Bajo, West Manggarai) - Anie A. Tuati; Deasi D. A. A. Daud; Ambrosius R. L. Wayan; Arnoldus Nama; Axceel J. Ndoen (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Labuan Bajo is the city center of West Manggarai Regency, known as a tourist city that has one of the seven wonders of the world, namely the Komodo Island tourist attraction, which makes Labuan Bajo city crowded with local and foreign tourists. There are several road sections in Labuan Bajo that are still ineffective due to certain factors. One of them is the performance of the Soekarno Hatta road section which is still ineffective due to the activities of food places (culinary tourism of the village end), docks, shops, hotels and offices that cause roadside obstacles that cause congestion. The performance of the road section is analyzed based on the Indonesian Road Capacity Guidelines (PKJI) in 2023. Based on the results of research and field observations, it shows that the large number of vehicles parked and stopped (side obstacles) on the road section is not balanced with parking facilities. This results in the actual speed of the road section becoming lower at 13 km / h. The performance of the road section based on the results of the saturation degree analysis (Q/C ratio) is at service level F with a saturation degree (DS) value of 1.08, with volume above road capacity, long queue, and low speed, because internal resistance is very high and drivers are starting to experience short-duration congestion.